Assessment of teachers and peers of ppg pjok students at partner schools - Norrochmah, Siti; Fitriady, Gema; Kurniawan, Rama; Wulandari, Ari Mei (Lambung Mangkurat University, 2025)
The purpose of this study was to assess the quality of the teaching module learning devices and the performance of Pre-Service Teacher Professional Education students in the subject of Physical Education, Sports, and Health at the State University of Malang Partner School. Using a cross-sectional study in the form of a quantitative descriptive with a data collection instrument in the form of a structured questionnaire using a Likert scale of 1-5. The subjects of the study were 142 PPG students in 2023 as respondents and 22 evaluators were mentor teachers from Partner schools. Data analysis used relative frequency (%) and a correlation test was carried out. This study assessed the quality of the teaching module and the performance of PPG PJOK students during PPL 2 at the State University of Malang partner school. As a result, more than 50% of students received a rating of